REPRESENTATION AND ANALYSIS OF QUOTATIONS IN BIOGRAPHICAL NOVEL “THE LAST STATION” (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article describes Jay Parini's biographical novel “The Last Station” and examines objectively and subjectively views the lives of characters and the use of intertextual means in this article. In modern literature, the place of the biographical novel was revealed through the work of Jay Parini.